BEST‐2K Method for Characterizing Dual‐Permeability Unsaturated Soils with Ponded and Tension Infiltrometers. Issue 1 (11th April 2019) - Lassabatere, Laurent; Di Prima, Simone; Bouarafa, Sofia; Iovino, Massimo; Bagarello, Vincenzo; Angulo-Jaramillo, Rafael
Abstract : Core Ideas: We present a new method for the hydraulic characterization of dual‐permeability soils. The BEST‐2K method was validated with synthetic soil data. The BEST‐2K method was also validated with real experimental data for contrasting soils. This study presents a new method (BEST‐2K) that extends the existing BEST methods for use in characterizing the water retention and hydraulic conductivity functions of matrix and fast‐flow regions in dual‐permeability soils. BEST‐2K requires input information from two water infiltration experiments that are performed under ponded (Beerkan) and unsaturated (tension infiltrometer) conditions at the surface. Other required inputs include water content measurements and the traditional BEST inputs (particle size distribution and bulk density). In this study, first, a flowchart of the BEST‐2K method was developed and illustrated with analytically generated data for a synthetic dual‐permeability soil. Next, a sensitivity analysis was performed to assess the accuracy of BEST‐2K and its sensitivity to the quality of the inputs (water contents and cumulative infiltrations, and the prior estimation of the volume ratio occupied by the fast‐flow region). Lastly, BEST‐2K was applied to real experimental data to characterize three soils that are prone to preferential flow. BEST‐2K was found to be a particularly useful tool that combines experimental and modeling approaches for characterizing dual‐permeability soils and, more generally, soils prone to preferential flows.